PERAN KELOMPOK MASYARAKAT MISKIN (POKMASKIN) DALAM PEMBERDAYAAN MASYARAKAT DI DESA WUKIRSARI KECAMATAN CANGKRINGAN KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - , Agus Ependi, S.Sos ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Poor Community Group (Pokmaskin) of Desa Wukirsari is a social agency originally engaging in activities to deal with the management of rice for the poor program. However, along with the dynamic evolvement of the group, it does not only focus on the matters of rice-the poor program, but later it develops into a community empowering agency with a number of empowerment activities. The effectiveness of the empowerment program through the program of work tool and financial credits is seen from the community participation in every stage of participation, ranging from problem identification, program formulation, program implementation and enjoyment of program results to the participation in evaluation program. Thud, their activive participation will lead to the effective of the Poor Community Group in implementing the community empowerment program. This a study case concerning the role of the Poor Community Group in empowering the community members. The method used in this study is qualitative-descriptive approach in which the author is trying to describe in a systematic and accurate manner the situation and characteristics of every phenomenon faced at field without intention of conducting statistical test. And data collection is done through structured and unstructured interviews and direct observation aiming at obtaining more accurate data. The findings conclude that at least there are two major things to be carefully viewed, namely (1) that the poor community participation is sufficiently good, particularly their participation in the non-empowerment program (management of rice-for-the poor program), while their participation in the empowerment activities like work tool ownership and work fund credits is very minor. Therefore, the partisipation is a quasi one, and (2) as a result of the quasi participation, the empowerment program, as a financial source of the program activities, becomes ineffective for the poor community. Otherwise, the empowerment program benefits most those elite group who never contributes much to the financial need of the Poor Commmunity Group.